2019
DOI: 10.1007/s10096-019-03514-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of viral load in the outcome of hospitalized patients with influenza virus infection

Abstract: The role of viral load in the outcome of patients requiring hospital admission due to influenza is not well established. We aim to assess if there is an association between the viral load and the outcome in hospitalized patients with a confirmed influenza virus infection. A retrospective observational study including all adult patients who were hospitalized in our center with a confirmed influenza virus infection from January to May 2016. Viral load was measured by real-time reverse-transcriptase-polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 25 publications
2
54
2
1
Order By: Relevance
“…6 The correlation of viral load with clinical outcome and disease severity has been investigated with different endemic respiratory viruses, but most results have not been conclusive. [9][10][11][12] However, in the case of prepandemic avian influenza H5N1, higher viral loads were associated with more severe disease and poorer outcome, 13 as seen with SARS-CoV-2 in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…6 The correlation of viral load with clinical outcome and disease severity has been investigated with different endemic respiratory viruses, but most results have not been conclusive. [9][10][11][12] However, in the case of prepandemic avian influenza H5N1, higher viral loads were associated with more severe disease and poorer outcome, 13 as seen with SARS-CoV-2 in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…had wider inclusion criteria and most patients were having acute respiratory infection, which might have been milder disease without fever. As expected, the median CRP was lower in our study compared to a study of hospitalized patients with influenza [ 21 ].…”
Section: Discussionsupporting
confidence: 84%
“…Several previous studies have looked at the relationship of viral load at diagnosis and the characteristics of the disease in patients with seasonal influenza [ 4 , 19–23 ]. The results of these studies have been mixed with some reporting associations [ 19–21 , 23–25 ] and others reporting no associations [ 4 , 22 ] with clinical characteristics of disease. The time since onset of symptoms and the viral load has been explored in 5 studies [ 4 , 19–21 , 23 ], and all but 1 found a relationship [ 23 , 25 ].…”
mentioning
confidence: 99%
“…The results of these studies have been mixed with some reporting associations [ 19–21 , 23–25 ] and others reporting no associations [ 4 , 22 ] with clinical characteristics of disease. The time since onset of symptoms and the viral load has been explored in 5 studies [ 4 , 19–21 , 23 ], and all but 1 found a relationship [ 23 , 25 ]. Two studies have looked at disease outcomes of hospitalized patients with influenza [ 23 , 25 ].…”
mentioning
confidence: 99%